A refractory material and its preparation method and application
By modifying plate-shaped corundum and artificial graphite materials, combining antioxidant and corrosion-resistant agents, the problems of short service life and poor thermal shock resistance in steelmaking continuous casting are solved, and high-quality skateboard performance is achieved. In the production of various molten steel.
Patent Information
- Application Number
- CN202410391244.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-02
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2044-04-02
AI Technical Summary
The existing skateboard bricks have a short service life, poor thermal shock resistance, large creep, and carbon elements are prone to seeping into the liquid steel, affecting the quality of the liquid steel, and are not resistant to corrosion to calcium-treated steel, which cannot meet high-quality production. need.
Using plate-shaped corundum modified coarse aggregate, modified artificial graphite, antioxidant, anti-erosion agent and binder, the material density and morphology are improved and the flush resistance is improved through the combination of coal gangue purification powder and nano-grade carbon black. and oxidation resistance, designed modified heat treatment and sintering processes to enhance the compressive strength and thermal shock stability of the material.
It significantly improves the service life of the skateboard, enhances the anti-shrink, erosion and oxidation properties, reduces the carbon content, and is suitable for pouring low-carbon steel and high-carbon steel, extending the service life of the skateboard to more than 5 times.
Smart Images

Figure BDA0004772408490000131 
Figure BDA0004772408490000141
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of refractory materials, and in particular relates to a refractory material and a preparation method thereof and an application thereof as a water outlet slide plate. Background Art
[0002] In the steelmaking continuous casting production process, the outlet of the converter, ladle or tundish is equipped with a slide plate. The slide plate is an important flow control component in the casting process of the continuous casting machine. The sliding of the slide plate can increase and decrease the water flow rate, so that the inflow and outflow of molten steel can be balanced, which is convenient for controlling the continuous casting operation. If the performance of the slide plate is poor, the service life of the slide plate is short, and it needs to be replaced frequently, which increases the replacement cost, affects the production efficiency, and even affects the quality of the molten steel.
[0003] Since the slide plate will be repeatedly subjected to physical scouring, chemical erosion and strong thermal shock of molten steel, as well as mechanical wear during sliding, higher performance requirements will be placed on the slide plate in converter, ladle or tundish components. The performance requirements for the slide plate generally include high temperature resistance, strength, wear resistance, erosion resistance, thermal shock resistance, scouring resistance, oxidation resistance and creep resistance.
[0004] The existing conventional skateboard bricks are made of refractory materials such as aluminum carbon, aluminum zirconium carbon, corundum, zirconium, corundum mullite, and magnesium crystal stone. Various raw materials are compounded with adhesives, pressed or poured, sintered, and other process steps to prepare skateboard bricks. Among them, although the carbon-containing skateboard bricks can improve the corrosion resistance and wear resistance, the carbon element is easily infiltrated into the molten steel when it is repeatedly washed, resulting in an increase in the carbon element in the molten steel, affecting the quality instability, and is not suitable for low-carbon molten steel production; in addition, the carbon-containing skateboard bricks have poor resistance to calcium oxide erosion and are not suitable for calcium-treated molten steel production; and the current non-carbon-containing skateboard bricks also generally have the problems of poor thermal shock resistance and large creep, resulting in a short service life.
[0005] With the demand for high-quality development in all aspects in recent years, all links of steelmaking and continuous casting are required to reduce costs, improve quality and increase efficiency. At present, the performance, quality and service life of conventional skateboards can no longer meet higher use requirements, so it is necessary to continuously develop and improve the preparation of high-quality skateboards. The existing general method to improve the performance of skateboard bricks is to adjust the particle size of various raw materials to improve the bonding tightness and density, thereby enhancing strength, anti-scouring, wear resistance, erosion resistance and other indicators; there are also methods to reduce the particle size and content of carbon to reduce the impact of carbon, but the effect is minimal, because the properties of various raw materials themselves limit the inability to significantly improve the performance of skateboard bricks. Summary of the invention
[0006] Various methods have been used to improve the performance of existing skateboard bricks, but the effect is minimal. The existing raw materials have their own advantages and disadvantages, which check and balance each other, limiting the overall improvement of various indicators of skateboard bricks, and there is still a problem that they cannot meet higher usage requirements. The present invention provides a refractory material and its preparation method and application, using materials such as plate-like corundum modified coarse aggregate, plate-like corundum fine aggregate and modified artificial graphite as raw materials, and using coal gangue purified powder and nano-grade carbon black to modify the plate-like corundum coarse aggregate, which has a smaller porosity and increases the volume density and strength. The modified artificial graphite has a certain improvement in compressive strength, thermal shock resistance, creep rate, etc. The modified plate-like corundum coarse aggregate and modified artificial graphite are used in combination to greatly improve the strength, good thermal shock stability, and low creep rate; the diameter of each hole expansion is small, the erosion resistance and corrosion resistance are good, and the carbon content entering the molten steel is very low, which will not significantly affect the carbon content of low-carbon molten steel. The specific technical scheme is as follows:
[0007] A refractory material is made of the following raw materials in parts by mass: 80 to 120 parts of plate-shaped corundum modified coarse aggregate, 50 to 90 parts of plate-shaped corundum fine aggregate, 2 to 6 parts of modified artificial graphite, 5 to 10 parts of antioxidant, 1 to 3 parts of anti-corrosion agent and 5 to 12 parts of adhesive;
[0008] The preparation method of the plate-like corundum modified coarse aggregate is as follows: according to the mass ratio of 3mm-5mm plate-like corundum coarse aggregate: 1.5mm-2.8mm plate-like corundum coarse aggregate = (0.3-0.8): (1.5-2.5), mixing to obtain plate-like corundum mixed coarse aggregate; using citric acid-fatty alcohol to soak coal gangue powder below 3μm in sodium sulfate aqueous solution for 3h-5h, and then filtering, washing and drying to obtain coal gangue purified powder; according to the mass ratio of plate-like corundum mixed coarse aggregate: coal gangue purified powder: nano-grade carbon black: water-soluble chitosan: aqueous defoamer: water = 100:
[0009] The material is prepared by wet ball milling for 30-50 min with a mass ratio of (0.5-3):(0.3-1.5):(2-5):(0.5-2):(30-50), and heat treatment is performed to obtain plate-shaped corundum modified coarse aggregate.
[0010] In the above technical method, the mass ratio of the components of the citric acid-fatty alcohol sodium sulfate aqueous solution is water: citric acid: fatty alcohol sodium sulfate = 100: (20-50): (3-5); the amount of the citric acid-fatty alcohol sodium sulfate aqueous solution is such that the water level covers the coal gangue powder.
[0011] In the above technical method, before wet ball milling, water-soluble chitosan, aqueous defoamer and water are premixed uniformly to obtain a mixed liquid, the purified coal gangue powder and nano-grade carbon black are premixed uniformly by air flow to obtain a mixed powder, and then the mixed liquid and the mixed powder are evenly mixed, and finally mixed with plate-like corundum mixed coarse aggregate and wet ball milled.
[0012] In the above technical method, the heat treatment is to dry the water at 60°C to 80°C, and then cure at 150°C to 250°C for 1h to 2h.
[0013] In the above technical method, the plate-shaped corundum modified fine aggregate is 0.1mm to 1mm.
[0014] In the above technical method, the preparation method of the modified artificial graphite is: according to the mass ratio of delayed petroleum coke powder: plate-like corundum powder: phenolic resin powder = 100: (3-8): (2-5), the phenolic resin powder below 2 μm and the plate-like corundum powder below 2 μm are first air-mixed evenly, and then added to the delayed petroleum coke powder of 10 μm to 80 μm, mixed to obtain a mixed powder, placed in a reactor, and subjected to a modified heat treatment at 300°C to 500°C, dispersed after cooling, and then graphitized at 2800°C to 3200°C to obtain modified artificial graphite.
[0015] In the above technical method, the stirring speed of the modified heat treatment is 50r / min~80r / min, and the time is 2h~2.5h; the heating curve of the graphitization is as follows: the starting temperature is room temperature, and the temperature is increased to 600℃~650℃ and kept for 30min~60min, and the temperature is increased to 1100℃~1300℃ and kept for 60min~90min, and the temperature is increased to 2800℃~3200℃ and kept for 2h~2.5h, and then cooled.
[0016] In the above technical method, the antioxidant is metallic silicon; the anti-corrosion agent is chromium oxide; and the adhesive is phenolic resin.
[0017] The above-mentioned method for preparing a refractory material comprises the following steps:
[0018] S1: First, plate-like corundum fine aggregate, antioxidant and anti-corrosion agent are mixed evenly in a double cone according to the mass fraction, and then modified artificial graphite is added and mixed evenly to obtain mixture A;
[0019] S2: Mixing material A, plate-shaped corundum modified coarse aggregate and binder by wheel mill according to mass proportions, and then placing them in a trapping chamber, heating and dehumidifying, trapping the materials for 15 to 20 days, and then pressing and molding them with a press pressure of 800 to 1000 tons to obtain bricks;
[0020] S3: sintering the bricks at 1500°C to 1650°C for 2h to 5h to obtain a refractory material.
[0021] The above-mentioned refractory material is used for making converter slide plates, ladle slide plates or tundish slide plates, and is used for steelmaking continuous casting of high-carbon molten steel, low-carbon molten steel or calcium-treated molten steel.
[0022] Compared with the prior art, the refractory material and the preparation method and application thereof of the present invention have the following beneficial effects:
[0023] 1. The refractory material of the present invention adopts plate-shaped corundum modified coarse aggregate, plate-shaped corundum fine aggregate, modified artificial graphite, antioxidant, anti-corrosion agent and adhesive as raw materials, wherein the plate-shaped corundum has good volume stability, extremely small reburning shrinkage, good thermal shock stability and bending strength; the antioxidant is metallic silicon, which has good wear resistance and oxidation resistance, and the anti-corrosion agent is chromium oxide, which has good corrosion resistance.
[0024] 2. The present invention designs a method for preparing platy corundum modified coarse aggregate: the gangue powder is first impregnated with a sodium sulfate aqueous solution of citric acid-fatty alcohol, and then washed with water to obtain a purified gangue powder, which can purify and improve the surface of the gangue powder, so that the gangue powder can be closely attached to the platy corundum mixed coarse aggregate. According to a certain proportion, the platy corundum mixed coarse aggregate, the purified gangue powder, nano-scale carbon black, water-soluble chitosan, aqueous defoamer and water are mixed and wet ball milled, which can improve the morphology of the platy corundum mixed coarse aggregate on the one hand, and on the other hand, the viscosity of the water-soluble chitosan is used to coat the purified gangue powder and nano-scale carbon black on the platy corundum mixed coarse aggregate, so as to make up for the surface defects and surface pores of the platy corundum mixed coarse aggregate and improve the density; on the other hand, the performance of the purified gangue powder and nano-scale carbon black is used to improve the erosion resistance and oxidation resistance of the platy corundum modified coarse aggregate particles.
[0025] 3. The present invention is designed to premix water-soluble chitosan, aqueous defoamer and water evenly before wet ball milling, premix the solvent in advance, and premix the purified gangue powder and nano-scale carbon black with air flow, so that the solid particles can be well dispersed later, that is, the nano-scale carbon black will not agglomerate after being added, preventing the nano-scale carbon black from losing its pore filling property.
[0026] 4. The present invention is designed to cure the plate-like corundum coarse aggregate after ball milling at 150°C to 250°C for 1h to 2h; this enables the coal gangue purified powder, nano-scale carbon black and chitosan to be tightly embedded in the pores and surface defects of the plate-like corundum coarse aggregate and not to peel off easily, thereby ensuring that the material structure of subsequent mixing is not destroyed in large quantities and the performance is not reduced.
[0027] Fifth, the present invention designs a preparation method of modified artificial graphite: phenolic resin powder below 2μm and plate-shaped corundum powder below 2μm are coated with delayed petroleum coke powder, and the delayed petroleum coke powder is modified. After sintering and graphitization, modified artificial graphite is obtained, wherein the delayed petroleum coke powder has a certain self-adhesiveness, and can bond small-sized phenolic resin powder and plate-shaped corundum powder. The thermosetting property of phenolic resin powder is utilized, and adhesion and curing is performed at 300℃~500℃ to obtain a core-shell structure with a stable structure. The graphite powder coated with plate-shaped corundum powder has better self-protection, and after the anti-corrosion brick blank is formed, it will not be easily exposed to the surface of the brick blank, nor will it be easily dissolved in molten steel, so as to prevent a substantial increase in the carbon content of the molten steel. In addition, the artificial graphite prepared by this method has better compatibility with other components than natural flake graphite, and the combination is more compact and strong after the pressed block is sintered, and the volume density, room temperature compressive strength, thermal shock resistance, creep resistance, high temperature flexural strength and other aspects are all enhanced.
[0028] 6. The modified stirring speed of delayed petroleum coke powder designed by the present invention is 50r / min~80r / min, and the time is 2h~2.5h. Under the condition of achieving uniform coating, it can ensure that the delayed petroleum coke powder is not stirred and crushed, and prevent the generation of a large amount of ultrafine powder, which affects the crack resistance of the subsequent briquetting. The graphitization heating curve is designed to have a starting temperature of room temperature, keep warm for 30min~60min when the temperature rises to 600℃~650℃, keep warm for 60min~90min when the temperature rises to 1100℃~1300℃, keep warm for 2h~2.5h when the temperature rises to 2800℃~3200℃, and then cool down. Staged insulation can give each material sufficient time when the particle carbon layer spacing changes, ensuring a stable transformation of material properties. 600℃~650℃ is the shrinkage temperature of the coating layer, 1100℃~1300℃ is the shrinkage temperature of the carbon layer of the delayed petroleum coke powder, and 2800℃~3200℃ is the graphitization temperature.
[0029] 7. The present invention designs a method for preparing refractory materials: first, the plate-like corundum fine aggregate, antioxidant and anti-corrosion agent are mixed evenly in a double cone, and then the modified artificial graphite is added; it can ensure that the modified artificial graphite is mixed evenly and the core-shell structure of the modified artificial graphite is not damaged as much as possible; the plate-like corundum modified coarse aggregate is designed to be added last for wheel mill mixing, which can reduce the particle friction damage on the surface of the plate-like corundum modified coarse aggregate caused by long-term mixing.
[0030] 8. Designing the trapped materials for 15 to 20 days can effectively remove moisture and exhaust air, make the material deposit dense, improve the compactness and density of the briquette, and then improve the strength and erosion resistance.
[0031] 9. Design the bricks to be sintered at 1500℃~1650℃ for 2h~5h. After high temperature curing, the bonding, strength, oxidation resistance, erosion resistance, seismic resistance, creep resistance and other properties of the material are improved.
[0032] In summary, the modified plate-like corundum coarse aggregate of the present invention has a smaller porosity, increased volume density and strength; in addition, the modified artificial graphite has certain improvements in compressive strength, thermal shock resistance, creep rate, etc. The modified plate-like corundum coarse aggregate and modified artificial graphite are used in combination to greatly improve strength, good thermal shock stability, and low creep rate. The refractory material of the present invention can be used as a skateboard to greatly extend its service life to more than 5 times; while the service life of a normal skateboard is 2 to 3 times. The carbon content of the refractory material of the present invention after preparing the skateboard is low, and the graphite component is not exposed to the surface of the skateboard. The diameter of each hole expansion is small, and the erosion resistance is good. Therefore, the carbon content entering the molten steel is very low, which will not greatly affect the carbon content of the low-carbon molten steel, and can be used for the pouring of low-carbon molten steel; it can also be used for the pouring of high-carbon molten steel and calcium-treated molten steel, and has good practical value. DETAILED DESCRIPTION
[0033] The present invention is further described below in conjunction with specific implementation cases, but the present invention is not limited to these embodiments.
[0034] Example 1
[0035] A refractory material is made of the following raw materials in parts by mass: 100 parts of plate-shaped corundum modified coarse aggregate, 70 parts of plate-shaped corundum fine aggregate, 4 parts of modified artificial graphite, 6 parts of antioxidant, 2 parts of anti-corrosion agent and 8 parts of adhesive; the plate-shaped corundum modified fine aggregate is 0.1mm-1mm; the antioxidant is metal silicon; the anti-corrosion agent is chromium oxide; and the adhesive is phenolic resin.
[0036] The preparation method of the plate-like corundum modified coarse aggregate is as follows: according to the mass ratio of 3mm-5mm plate-like corundum coarse aggregate: 1.5mm-2.8mm plate-like corundum coarse aggregate = 0.5:1.8, the plate-like corundum mixed coarse aggregate is mixed; the coal gangue powder below 3μm is impregnated with a citric acid-fatty alcohol sodium sulfate aqueous solution for 4h, and the amount of the citric acid-fatty alcohol sodium sulfate aqueous solution is such that the water level covers the coal gangue powder; then, it is filtered, washed with water, and dried to obtain the coal gangue purified powder; according to the mass ratio of plate-like corundum mixed coarse aggregate: coal gangue purified The mass ratio of powder: nano-scale carbon black: water-soluble chitosan: aqueous defoamer: water = 100:2:1:3:1:40, first pre-mix water-soluble chitosan, aqueous defoamer and water to obtain a mixed solution, pre-mix the purified coal gangue powder and nano-scale carbon black in an airflow to obtain a mixed powder, then mix the mixed solution and the mixed powder, and finally mix with the plate-like corundum mixed coarse aggregate, wet ball mill for 40 minutes, dry the water at 70°C, and then cure at 200°C for 1.5 hours to obtain the plate-like corundum modified coarse aggregate. Among them, the mass ratio of the citric acid-fatty alcohol sodium sulfate aqueous solution is water: citric acid: fatty alcohol sodium sulfate = 100:35:4.
[0037] The preparation method of modified artificial graphite is as follows: according to the mass ratio of delayed petroleum coke powder: plate-shaped corundum powder: phenolic resin powder = 100:5:3, phenolic resin powder below 2μm and plate-shaped corundum powder below 2μm are first mixed uniformly by air flow, and then added to delayed petroleum coke powder of 10μm to 80μm, mixed to obtain mixed powder, placed in a reactor, subjected to modified heat treatment at 400℃ for 2h, stirring at a speed of 60r / min, dispersed after cooling, and then graphitized at 3000℃ to obtain modified artificial graphite. The graphitization heating curve is as follows: the starting temperature is room temperature, the temperature is kept at 620℃ for 40min, the temperature is kept at 1200℃ for 70min, the temperature is kept at 3000℃ for 2h, and then the temperature is lowered.
[0038] The above-mentioned method for preparing a refractory material comprises the following steps:
[0039] S1: First, plate-like corundum fine aggregate, antioxidant and anti-corrosion agent are mixed evenly in a double cone according to the mass fraction, and then modified artificial graphite is added and mixed evenly to obtain mixture A;
[0040] S2: Mixture A, plate-shaped corundum modified coarse aggregate and binder are mixed by a roller mill according to their mass fractions, and then placed in a trapped material chamber for heating and dehumidification. After trapped for 16 days, a 1000-ton press is used to press and form the bricks;
[0041] S3: Sinter the bricks at 1600°C for 3 hours to obtain refractory materials.
[0042] The above-mentioned refractory material is used for making converter slide plates, ladle slide plates or tundish slide plates, and is used for steelmaking continuous casting of high-carbon molten steel, low-carbon molten steel or calcium-treated molten steel.
[0043] The skateboard brick blank sample prepared in this embodiment has the following specifications: length and width 100mm×90mm, thickness 30mm, and hole diameter 28mm.
[0044] Example 2
[0045] A refractory material is made of the following raw materials in parts by mass: 90 parts of plate-shaped corundum modified coarse aggregate, 60 parts of plate-shaped corundum fine aggregate, 3 parts of modified artificial graphite, 6 parts of antioxidant, 1.5 parts of anti-corrosion agent and 6 parts of adhesive; the plate-shaped corundum modified fine aggregate is 0.1 mm to 1 mm; the antioxidant is metal silicon; the anti-corrosion agent is chromium oxide; and the adhesive is phenolic resin.
[0046] The preparation method of the plate-like corundum modified coarse aggregate is as follows: according to the mass ratio of 3mm-5mm plate-like corundum coarse aggregate: 1.5mm-2.8mm plate-like corundum coarse aggregate = 0.4:1.7, the plate-like corundum mixed coarse aggregate is mixed; the coal gangue powder below 3μm is impregnated with a citric acid-fatty alcohol sodium sulfate aqueous solution for 3.5h, and the amount of the citric acid-fatty alcohol sodium sulfate aqueous solution is such that the water level covers the coal gangue powder; then, it is filtered, washed with water, and dried to obtain the coal gangue purified powder; according to the mass ratio of plate-like corundum mixed coarse aggregate: coal gangue purified The mass ratio of powder: nano-scale carbon black: water-soluble chitosan: aqueous defoamer: water = 100:1:0.5:3:0.8:35, first pre-mix water-soluble chitosan, aqueous defoamer and water to obtain a mixed solution, pre-mix the purified coal gangue powder and nano-scale carbon black in an airflow to obtain a mixed powder, then mix the mixed solution and the mixed powder, and finally mix with the plate-like corundum mixed coarse aggregate, wet ball mill for 35 minutes, dry the water at 65°C, and then cure at 180°C for 1 hour to obtain the plate-like corundum modified coarse aggregate. Among them, the mass ratio of the citric acid-fatty alcohol sodium sulfate aqueous solution is water: citric acid: fatty alcohol sodium sulfate = 100:25:3.5.
[0047] The preparation method of modified artificial graphite is as follows: according to the mass ratio of delayed petroleum coke powder: plate-shaped corundum powder: phenolic resin powder = 100:4:3, the phenolic resin powder below 2μm and the plate-shaped corundum powder below 2μm are first mixed uniformly by air flow, and then added to the delayed petroleum coke powder of 10μm to 80μm, mixed to obtain a mixed powder, placed in a reactor, and subjected to a modified heat treatment at 350°C for 2h, with a stirring speed of 60r / min, and then dispersed after cooling, and then graphitized at 2900°C to obtain modified artificial graphite. The graphitization heating curve is as follows: the starting temperature is room temperature, the temperature is kept at 610°C for 35min, the temperature is kept at 1150°C for 70min, the temperature is kept at 2900°C for 2h, and then the temperature is lowered.
[0048] The above-mentioned method for preparing a refractory material comprises the following steps:
[0049] S1: First, plate-like corundum fine aggregate, antioxidant and anti-corrosion agent are mixed evenly in a double cone according to the mass fraction, and then modified artificial graphite is added and mixed evenly to obtain mixture A;
[0050] S2: Mixture A, plate-shaped corundum modified coarse aggregate and binder are mixed by a roller mill according to their mass fractions, and then placed in a trapped material chamber for heating and dehumidification. After trapped for 17 days, they are pressed and formed by a 850-ton press to obtain a brick blank;
[0051] S3: Sinter the bricks at 1550°C for 2.5 hours to obtain refractory materials.
[0052] The above-mentioned refractory material is used for making converter slide plates, ladle slide plates or tundish slide plates, and is used for steelmaking continuous casting of high-carbon molten steel, low-carbon molten steel or calcium-treated molten steel.
[0053] The skateboard brick blank sample prepared in this embodiment has the following specifications: length and width 100mm×90mm, thickness 30mm, and hole diameter 28mm.
[0054] Example 3
[0055] A refractory material is made of the following raw materials in parts by mass: 110 parts of plate-shaped corundum modified coarse aggregate, 80 parts of plate-shaped corundum fine aggregate, 5 parts of modified artificial graphite, 9 parts of antioxidant, 2.5 parts of anti-corrosion agent and 10 parts of adhesive; the plate-shaped corundum modified fine aggregate is 0.1 mm to 1 mm; the antioxidant is metal silicon; the anti-corrosion agent is chromium oxide; and the adhesive is phenolic resin.
[0056] Among them, the preparation method of plate-like corundum modified coarse aggregate is as follows: according to the mass ratio of 3mm~5mm plate-like corundum coarse aggregate: 1.5mm~2.8mm plate-like corundum coarse aggregate = 0.7:2.2, mixing to obtain plate-like corundum mixed coarse aggregate; impregnating coal gangue powder below 3μm with citric acid-fatty alcohol sodium sulfate aqueous solution for 4.5h, and the amount of citric acid-fatty alcohol sodium sulfate aqueous solution is such that the water level covers the coal gangue powder; then filtering, washing, and drying to obtain coal gangue purified powder; according to the mixed coarse aggregate of plate-like corundum: coal gangue purified powder: The mass ratio of nano-scale carbon black: water-soluble chitosan: water-based defoamer: water = 100:2.5:1.2:4.5:1.5:45, first pre-mix water-soluble chitosan, water-based defoamer and water to obtain a mixed solution, pre-mix the coal gangue purified powder and nano-scale carbon black in an airflow to obtain a mixed powder, then mix the mixed solution and the mixed powder, and finally mix with the plate-like corundum mixed coarse aggregate, wet ball mill for 45 minutes, dry the water at 75°C, and then cure at 220°C for 2 hours to obtain the plate-like corundum modified coarse aggregate. Among them, the mass ratio of the citric acid-fatty alcohol sodium sulfate aqueous solution is water: citric acid: fatty alcohol sodium sulfate = 100:45:4.
[0057] The preparation method of modified artificial graphite is as follows: according to the mass ratio of delayed petroleum coke powder: plate-shaped corundum powder: phenolic resin powder = 100:7:4, the phenolic resin powder below 2μm and the plate-shaped corundum powder below 2μm are first mixed uniformly by air flow, and then added to the delayed petroleum coke powder of 10μm to 80μm, mixed to obtain a mixed powder, placed in a reactor, and subjected to a modified heat treatment at 450°C for 2.5h, with a stirring speed of 70r / min, and then dispersed after cooling, and then graphitized at 3100°C to obtain modified artificial graphite. The graphitization heating curve is as follows: the starting temperature is room temperature, the temperature is kept at 640°C for 55min, the temperature is kept at 1250°C for 80min, the temperature is kept at 3100°C for 2.5h, and then the temperature is lowered.
[0058] The above-mentioned method for preparing a refractory material comprises the following steps:
[0059] S1: First, plate-like corundum fine aggregate, antioxidant and anti-corrosion agent are mixed evenly in a double cone according to the mass fraction, and then modified artificial graphite is added and mixed evenly to obtain mixture A;
[0060] S2: Mixture A, plate-shaped corundum modified coarse aggregate and binder are mixed by a roller mill according to their mass fractions, and then placed in a trapped material chamber for heating and dehumidification. After trapped for 18 days, a 1000-ton press is used to press and form the bricks;
[0061] S3: Sinter the bricks at 1600°C for 4 hours to obtain refractory materials.
[0062] The above-mentioned refractory material is used for making converter slide plates, ladle slide plates or tundish slide plates, and is used for steelmaking continuous casting of high-carbon molten steel, low-carbon molten steel or calcium-treated molten steel.
[0063] The skateboard brick blank sample prepared in this embodiment has the following specifications: length and width 100mm×90mm, thickness 30mm, and hole diameter 28mm.
[0064] Example 4
[0065] A refractory material is made of the following raw materials in parts by mass: 80 parts of plate-shaped corundum modified coarse aggregate, 50 parts of plate-shaped corundum fine aggregate, 2 parts of modified artificial graphite, 5 parts of antioxidant, 1 part of anti-corrosion agent and 5 parts of adhesive; the plate-shaped corundum modified fine aggregate is 0.1 mm to 1 mm; the antioxidant is metal silicon; the anti-corrosion agent is chromium oxide; and the adhesive is phenolic resin.
[0066] Among them, the preparation method of the plate-like corundum modified coarse aggregate is as follows: according to the mass ratio of 3mm~5mm plate-like corundum coarse aggregate: 1.5mm~2.8mm plate-like corundum coarse aggregate = 0.3:1.5, mixing to obtain plate-like corundum mixed coarse aggregate; impregnating the coal gangue powder below 3μm with citric acid-fatty alcohol sodium sulfate aqueous solution for 3h, and the amount of citric acid-fatty alcohol sodium sulfate aqueous solution is such that the water level covers the coal gangue powder; then filtering, washing, and drying to obtain coal gangue purified powder; according to the plate-like corundum mixed coarse aggregate: coal gangue purified powder: The mass ratio of nano-scale carbon black: water-soluble chitosan: water-based defoamer: water = 100: 0.5: 0.3: 2: 0.5: 30, first pre-mix the water-soluble chitosan, water-based defoamer and water to obtain a mixed solution, pre-mix the coal gangue purified powder and nano-scale carbon black in an airflow to obtain a mixed powder, then evenly mix the mixed solution and the mixed powder, and finally mix with the plate-like corundum mixed coarse aggregate, wet ball mill for 30 minutes, dry the water at 60°C, and then cure at 150°C for 1 hour to obtain the plate-like corundum modified coarse aggregate. Among them, the mass ratio of the citric acid-fatty alcohol sodium sulfate aqueous solution is water: citric acid: fatty alcohol sodium sulfate = 100: 20: 3.
[0067] The preparation method of modified artificial graphite is as follows: according to the mass ratio of delayed petroleum coke powder: plate-shaped corundum powder: phenolic resin powder = 100:3:2, the phenolic resin powder below 2μm and the plate-shaped corundum powder below 2μm are first mixed uniformly by air flow, and then added to the delayed petroleum coke powder of 10μm to 80μm, mixed to obtain a mixed powder, placed in a reactor, and subjected to a modified heat treatment at 300°C for 2h, with a stirring speed of 50r / min, and then dispersed after cooling, and then graphitized at 2800°C to obtain modified artificial graphite. The graphitization temperature rise curve is as follows: the starting temperature is room temperature, the temperature is kept at 600°C for 30min to 60min, the temperature is kept at 1100°C for 60min, the temperature is kept at 2800°C for 2h, and then the temperature is lowered.
[0068] The above-mentioned method for preparing a refractory material comprises the following steps:
[0069] S1: First, plate-like corundum fine aggregate, antioxidant and anti-corrosion agent are mixed evenly in a double cone according to the mass fraction, and then modified artificial graphite is added and mixed evenly to obtain mixture A;
[0070] S2: Mixture A, plate-shaped corundum modified coarse aggregate and binder are mixed by a roller mill according to their mass fractions, and then placed in a trapped material chamber for heating and dehumidification. After trapped for 15 days, they are pressed and formed by a 800-ton press to obtain a brick blank;
[0071] S3: Sinter the bricks at 1500°C for 2 hours to obtain refractory materials.
[0072] The above-mentioned refractory material is used for making converter slide plates, ladle slide plates or tundish slide plates, and is used for steelmaking continuous casting of high-carbon molten steel, low-carbon molten steel or calcium-treated molten steel.
[0073] The skateboard brick blank sample prepared in this embodiment has the following specifications: length and width 100mm×90mm, thickness 30mm, and hole diameter 28mm.
[0074] Example 5
[0075] A refractory material is made of the following raw materials in parts by mass: 120 parts of plate-shaped corundum modified coarse aggregate, 90 parts of plate-shaped corundum fine aggregate, 6 parts of modified artificial graphite, 10 parts of antioxidant, 3 parts of anti-corrosion agent and 12 parts of adhesive; the plate-shaped corundum modified fine aggregate is 0.1 mm to 1 mm; the antioxidant is metal silicon; the anti-corrosion agent is chromium oxide; and the adhesive is phenolic resin.
[0076] The preparation method of the plate-like corundum modified coarse aggregate is as follows: according to the mass ratio of 3mm-5mm plate-like corundum coarse aggregate: 1.5mm-2.8mm plate-like corundum coarse aggregate = 0.8:2.5, the plate-like corundum mixed coarse aggregate is mixed; the coal gangue powder below 3μm is impregnated with a citric acid-fatty alcohol sodium sulfate aqueous solution for 5h, and the amount of the citric acid-fatty alcohol sodium sulfate aqueous solution is such that the water level covers the coal gangue powder; then, it is filtered, washed with water, and dried to obtain the coal gangue purified powder; according to the mass ratio of plate-like corundum mixed coarse aggregate: coal gangue purified The mass ratio of powder: nano-scale carbon black: water-soluble chitosan: water-based defoamer: water = 100:3:1.5:5:2:50, first pre-mix water-soluble chitosan, water-based defoamer and water to obtain a mixed solution, pre-mix the purified coal gangue powder and nano-scale carbon black in an airflow to obtain a mixed powder, then mix the mixed solution and the mixed powder, and finally mix with the plate-like corundum mixed coarse aggregate, wet ball mill for 50 minutes, dry the water at 80°C, and then cure at 250°C for 2 hours to obtain the plate-like corundum modified coarse aggregate. Among them, the mass ratio of the citric acid-fatty alcohol sodium sulfate aqueous solution is water: citric acid: fatty alcohol sodium sulfate = 100:50:5.
[0077] The preparation method of modified artificial graphite is as follows: according to the mass ratio of delayed petroleum coke powder: plate-shaped corundum powder: phenolic resin powder = 100:8:5, the phenolic resin powder below 2μm and the plate-shaped corundum powder below 2μm are first mixed uniformly by air flow, and then added to the delayed petroleum coke powder of 10μm to 80μm, mixed to obtain a mixed powder, placed in a reactor, and subjected to a modified heat treatment at 500°C for 2.5h, with a stirring speed of 80r / min, and then dispersed after cooling, and then graphitized at 3200°C to obtain modified artificial graphite. The graphitization heating curve is as follows: the starting temperature is room temperature, the temperature is kept at 650°C for 30min to 60min, the temperature is kept at 1300°C for 90min, the temperature is kept at 3200°C for 2.5h, and then the temperature is lowered.
[0078] The above-mentioned method for preparing a refractory material comprises the following steps:
[0079] S1: First, plate-like corundum fine aggregate, antioxidant and anti-corrosion agent are mixed evenly in a double cone according to the mass fraction, and then modified artificial graphite is added and mixed evenly to obtain mixture A;
[0080] S2: Mixture A, plate-shaped corundum modified coarse aggregate and binder are mixed by a roller mill according to their mass fractions, and then placed in a trapped material chamber for heating and dehumidification. After trapped for 20 days, a 1000-ton press is used to press and form the bricks;
[0081] S3: Sinter the bricks at 1650°C for 5 hours to obtain refractory materials.
[0082] The above-mentioned refractory material is used for making converter slide plates, ladle slide plates or tundish slide plates, and is used for steelmaking continuous casting of high-carbon molten steel, low-carbon molten steel or calcium-treated molten steel.
[0083] The skateboard brick blank sample prepared in this embodiment has the following specifications: length and width 100mm×90mm, thickness 30mm, and hole diameter 28mm.
[0084] Preparation of Comparative Example 1 Sample
[0085] In the refractory material, the plate-shaped corundum coarse aggregate is not modified, and the plate-shaped corundum mixed coarse aggregate is directly used. Other parameters and methods are the same as those in Example 1.
[0086] Preparation of Comparative Example 2 Samples
[0087] In the refractory material, the plate-like corundum coarse aggregate is not modified, and the plate-like corundum mixed coarse aggregate is directly used; however, 2 parts of coal gangue powder and 1 part of nano-scale carbon black are added to the refractory material and mixed and added in step S1 of the preparation method; other parameters and methods are the same as in Example 1.
[0088] Preparation of Comparative Example 3 Samples
[0089] In the refractory material, the modified artificial graphite is replaced by natural flake graphite with a diameter of 10 μm to 80 μm. Other parameters and methods are the same as those in Example 1.
[0090] Preparation of Comparative Example 4 Samples
[0091] In the refractory material, the plate-shaped corundum coarse aggregate is not modified, and the plate-shaped corundum mixed coarse aggregate is directly used; and the modified artificial graphite is replaced by natural flake graphite with a diameter of 10 μm to 80 μm. Other parameters and methods are the same as those in Example 1.
[0092] Preparation of Comparative Example 5 Samples
[0093] In the refractory material, the gangue powder is not purified by citric acid-fatty alcohol sodium sulfate aqueous solution, the plate-like corundum coarse aggregate is modified by directly adding the raw gangue powder, and the other parameters and methods are the same as those in Example 1.
[0094] The performance of the skateboard brick blank samples of each embodiment and the skateboard brick blank samples of each comparative example was tested, and the results are shown in Table 1 below:
[0095] Table 1 Performance test results
[0096]
[0097] It can be seen from the above results that the performance results of the samples of Examples 1 to 5 are very good. From the data of the comparative example, it can be seen that the performance of the samples can be greatly affected if the plate-like corundum coarse aggregate is not modified. The modified plate-like corundum coarse aggregate has a smaller porosity, increased volume density and strength; in addition, the modified artificial graphite has a certain improvement in compressive strength, thermal shock resistance, creep rate, etc. The modified plate-like corundum coarse aggregate and modified artificial graphite are used together to greatly improve the strength, good thermal shock stability, and low creep rate. The purified coal gangue powder can improve the modified bonding and improve the performance of the plate-like corundum coarse aggregate in the brick.
[0098] Three pieces of each batch of brick samples were taken, and after post-processing such as steel ring hooping and grinding, they were made into finished skateboards. They were cast with low-carbon steel in a medium-sized ladle for trial use. The results are shown in Table 2 below:
[0099] Table 2 Service life test
[0100]
[0101] From the above results, it can be seen that the slides of Examples 1 to 5 can be used 5 times, which greatly extends the service life. The service life of a normal slide is 2 to 3 times. The carbon content in the slide is low, and the diameter of each hole expansion is small. Therefore, the carbon content entering the molten steel is very low, which will not greatly affect the carbon content of low-carbon molten steel. It can be used for the pouring of low-carbon molten steel; it can also be used for the pouring of high-carbon molten steel and calcium-treated molten steel. In addition, the purified coal gangue powder can improve the modified bonding of the plate-like corundum coarse aggregate, and then the scouring resistance of the slide; the unpurified coal gangue powder will affect the bonding of the material and reduce the scouring resistance.
Claims
1. A refractory material, characterized in that: The invention is prepared from the following raw materials in parts by weight: 80 to 120 parts of plate-shaped corundum modified coarse aggregate, 50 to 90 parts of plate-shaped corundum fine aggregate, 2 to 6 parts of modified artificial graphite, 5 to 10 parts of antioxidant, 1 to 3 parts of anti-corrosion agent and 5 to 12 parts of adhesive; The preparation method of the plate-shaped corundum modified coarse aggregate is: According to the mass ratio of 3mm~5mm plate-shaped corundum coarse aggregate: 1.5mm~2.8mm plate-shaped corundum coarse aggregate = (0.3~0.8): (1.5~2.5), the plate-shaped corundum mixed coarse aggregate is obtained; the coal gangue powder below 3μm is first impregnated with a sodium sulfate aqueous solution of citric acid-fatty alcohol for 3h~5h, and then filtered, washed with water, and dried to obtain the coal gangue purified powder; according to the mass ratio of plate-shaped corundum mixed coarse aggregate: coal gangue Purified powder: nano-grade carbon black: water-soluble chitosan: water-based defoamer: water = 100: (0.5-3): (0.3-1.5): (2-5): (0.5-2): (30-50) mass ratio, wet ball milling for 30-50 minutes, heat treatment, the heat treatment is drying the water at 60-80 degrees Celsius, and then curing at 150-250 degrees Celsius for 1 hour to 2 hours; obtain plate-shaped corundum modified coarse aggregate; The mass ratio of the citric acid-fatty alcohol sodium sulfate aqueous solution is water: citric acid: fatty alcohol sodium sulfate = 100: (20-50): (3-5); The preparation method of the modified artificial graphite comprises: firstly, in a mass ratio of delayed petroleum coke powder: plate-shaped corundum powder: phenolic resin powder = 100: (3-8): (2-5), uniformly mixing phenolic resin powder below 2 μm and plate-shaped corundum powder below 2 μm by air flow, then adding the mixture to delayed petroleum coke powder of 10 μm to 80 μm, mixing to obtain a mixed powder, placing the mixture in a reactor, performing a modified heat treatment at 300° C. to 500° C., breaking up the mixture after cooling, and then graphitizing the mixture at 2800° C. to 3200° C. to obtain the modified artificial graphite; The stirring speed of the modified heat treatment is 50r / min-80r / min, and the time is 2h-2.5h; the graphitization heating curve is as follows: the starting temperature is room temperature, and when the temperature rises to 600℃-650℃, it is kept warm for 30min-60min, when the temperature rises to 1100℃-1300℃, it is kept warm for 60min-90min, when the temperature rises to 2800℃-3200℃, it is kept warm for 2h-2.5h, and then the temperature is lowered; The preparation method of the refractory material comprises the following steps: S1: First, plate-like corundum fine aggregate, antioxidant and anti-corrosion agent are mixed evenly in a double cone according to the mass fraction, and then modified artificial graphite is added and mixed evenly to obtain mixture A; S2: Mixing material A, plate-shaped corundum modified coarse aggregate and binder by wheel mill according to mass proportions, and then placing them in a trapping chamber, heating and dehumidifying, trapping the materials for 15 to 20 days, and then pressing and molding them with a press pressure of 800 to 1000 tons to obtain bricks; S3: sintering the bricks at 1500°C to 1650°C for 2h to 5h to obtain a refractory material.
2. A refractory material according to claim 1, characterized in that: The amount of the citric acid-fatty alcohol sodium sulfate aqueous solution is such that the water level covers the coal gangue powder.
3. A refractory material according to claim 1, characterized in that: Before wet ball milling, water-soluble chitosan, aqueous defoamer and water are premixed uniformly to obtain a mixed liquid, and the purified coal gangue powder and nano-grade carbon black are premixed uniformly by air flow to obtain a mixed powder, and then the mixed liquid and the mixed powder are uniformly mixed, and finally mixed with plate-like corundum mixed coarse aggregate and wet ball milled.
4. A refractory material according to claim 1, characterized in that: The plate-shaped corundum modified fine aggregate is 0.1 mm to 1 mm.
5. A refractory material according to claim 1, characterized in that: The antioxidant is metal silicon; the anti-corrosion agent is chromium oxide; and the adhesive is phenolic resin.
6. Use of a refractory material according to any one of claims 1 to 5, characterized in that: Refractory materials are used to make converter slides, ladle slides or tundish slides, and are used for steelmaking and continuous casting of high-carbon molten steel, low-carbon molten steel or calcium-treated molten steel.
Citation Information
Patent Citations
In-situ generated CM2A8 multiphase reinforced steel ladle casting material and preparation method thereof
CN106699141A
Modified graphite-containing low-carbon sliding brick for converter slag blockage, and preparation method thereof
CN107602099A
